Molecular detection of ancylostoma duodenale, ancylostoma ceylanicum, and necator americanus in humans in northeastern and southern Thailand - Issarapong Phosuk (2018)
The 2 principal species of hookworms infecting humans are Necator americanus and Ancylostoma duodenale. Case studies on zoonotic hookworm infections with Ancylostoma ceylanicum and/or Ancylostoma caninum are known mainly from Asian countries. Of these 2 zoonotic species, only A. ceylanicum can develop to adulthood in humans. In the present study, we report a molecular-based survey of human hookworm infections present in southern and northeastern Thailand. Thirty larval hookworm samples were obtained from fecal agar plate cultures of 10 patients in northeastren Thailand and 20 in southern Thailand. Partial ITS1, 5.8S, and ITS2 regions of the ribosomal DNA genes were amplified using PCR. The amplicons were sequenced, aligned, and compared with other hookworm sequences in GenBank database. The results showed that, in Thailand, N. americanus is more prevalent than Ancylostoma spp. and is found in both study areas. Sporadic cases of A. ceylanicum and A. duodenale infection were seen in northeastern Thailand. © 2013, Korean Society for Parasitology and Tropical Medicine.